2021
DOI: 10.1177/21501327211030120
|View full text |Cite
|
Sign up to set email alerts
|

Can Type of Dizziness Influence the Vestibular Caloric Test Result?

Abstract: Background: The broad range of vestibular tests used to diagnose labyrinth diseases allows for a functional assessment of the vestibular system. Among the many tests performed, the caloric test is considered the gold standard by providing an objective measurement of the vestibular function for each labyrinth. Objective: to correlate the different types of dizziness with the caloric test result. Methods: a descriptive study was performed based on the previous records of vestibular tests performed on patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(74 reference statements)
0
3
0
2
Order By: Relevance
“…In our study, unilateral vestibular weakness was observed in 39.7%, abnormal results of the caloric test were present in 36.2%, and changes in oculomotor movements in around 40% (Table 3). These findings disclose an unexpected degree of neurological alterations after a vestibular disease post-COVID-19, when compared to the general population that presented a vestibular disease (24,25). A study in the adult US population found a prevalence of vestibular hypofunction of 28/100,000 (26).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In our study, unilateral vestibular weakness was observed in 39.7%, abnormal results of the caloric test were present in 36.2%, and changes in oculomotor movements in around 40% (Table 3). These findings disclose an unexpected degree of neurological alterations after a vestibular disease post-COVID-19, when compared to the general population that presented a vestibular disease (24,25). A study in the adult US population found a prevalence of vestibular hypofunction of 28/100,000 (26).…”
Section: Discussionmentioning
confidence: 65%
“…In a descriptive study by Felipe et al, patients with body balance disorders revealed peripheral disease in 40.1% and central disease in 2.5% individuals. Abnormal results in the caloric test were found in 42.6%, with UW present in 31.7% patients with vertigo ( 24 ). The other study that analyzed VNG in patients with dizziness, vertigo, and balance disorders revealed vestibular disorders in 35.86% patients, benign paroxysmal positional vertigo in 18.9% of patients, mixed vertigo in 16.12% of patients, cervical vertigo in 5.42% of patients, vertigo and dizziness of central origin in 3.78% of patients, vascular vertigo in 2.8% of patients, and vestibular neuritis in 2.3% of patients ( 25 ).…”
Section: Discussionmentioning
confidence: 97%
“…Перевірка допомогою калоричної та обертальної проб є неприйнятними для дітей через стимуляцію запаморочення та нудоти [35], а на тест вестибулярних викликаних міогенних потенціалів (VEMP) негативно впливає наявність випоту в середньому вусі [31].…”
Section: вступunclassified
“…For a better study of motion sickness, as well as to evaluate the possibilities of therapies and drug treatments, some motion sickness provocation models were used (16)(17)(18)(19) . One of the first models was labyrinthine stimulation with air and water, which attempts to simulate labyrinthine functioning, although the endolymphatic current velocity achieved in the caloric test was very low and nonphysiological (17) .…”
Section: Introductionmentioning
confidence: 99%